Proteomic analysis reveals differential accumulation of small heat shock proteins and late embryogenesis abundant proteins between ABA-deficient mutant vp5 seeds and wild-type Vp5 seeds in maize - Wu, Xiaolin; Gong, Fangping; Yang, Le; Hu, Xiuli; Tai, Fuju; Wang, Wei (Frontiers in Plant Science, 2015)
ABA is a major plant hormone that plays important roles during many phases of plant life cycle, including seed development, maturity and dormancy, and especially the acquisition of desiccation tolerance. Understanding of the molecular basis of ABA-mediated plant response to stress is of interest not only in basic research on plant adaptation but also in applied research on plant productivity. Maize mutant viviparous-5 (vp5), deficient in ABA biosynthesis in seeds, is a useful material for studying ABA-mediated response in maize. Due to carotenoid deficiency, vp5 endosperm is white, compared to yellow Vp5 endosperm. However, the background difference at proteome level between vp5 and Vp5 seeds is unclear. This study aimed to characterize proteome alterations of maize vp5 seeds and to identify ABA-dependent proteins during seed maturation. We compared the embryo and endosperm proteomes of vp5 and Vp5 seeds by gel-based proteomics. Up to 46 protein spots, most in embryos, were found to be differentially accumulated between vp5 and Vp5. The identified proteins included small heat shock proteins (sHSPs), late embryogenesis abundant (LEA) proteins, stress proteins, storage proteins and enzymes among others. However, EMB564, the most abundant LEA protein in maize embryo, accumulated in comparable levels between vp5 and Vp5 embryos, which contrasted to previously characterized, greatly lowered expression of emb564 mRNA in vp5 embryos. Moreover, LEA proteins and sHSPs displayed differential accumulations in vp5 embryos: six out of eight identified LEA proteins decreased while nine sHSPs increased in abundance. Finally, we discussed the possible causes of global proteome alterations, especially the observed differential accumulation of identified LEA proteins and sHSPs in vp5 embryos. The data derived from this study provides new insight into ABA-dependent proteins and ABA-mediated response during maize seed maturation.